Reformasi Birokrasi Dan Pelayanan Publik - Muhammad Dawud Shoimuna (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of writing reform papers is improvement; bureaucratic reform means a change of perspective, an increase in